119k views
2 votes
Describe your thinking and the steps taken when developing an

algebraic representation for the sum of the first t terms of a
linear sequence.

1 Answer

1 vote

Let's see what to do buddy...

_________________________________

Step (1)

Suppose we want to find the sum of numbers from 1 to n.

To do this, we use the following method.

By writing the sum of numbers from 1 to n

, Then we write the sum of numbers n to 1 below it, see :


s = 1 + 2 + 3 + ... + n


s = n + (n - 1) + (n - 2) + ... + 1 \\

Now we add the sentences of the above two phrases, peer to peer like this :


1 + n = n + 1 \\


2 + n - 1 = n + 1


3 + n - 2 = n + 1

And the others.....

So we have :


2s = ( n + 1) + (n + 1) + ... + (n + 1) \\

We had n numbers to sum so we have :


2s = n * (n + 1)

Divided the sides of the equation by 2


s = (n * (n + 1))/(2) \\

Remember this step I will use it again.

_________________________________

Step (2)

What does the linear sequence mean ?

The linear sequence is the sequence which any terms created by the sum of previous term with constant.

I name that constant value d.

According to above :


t(2) = t(1) + d

And


t(3) = t(2) + d


t(3) = t(1) + d + d


t(3) = t(1) + 2d

I have a question ;


3 - 1 = 2

Is it correct ?

If it is correct we have :


t(3) = t(1) + (3 - 1)d

WOW we found a thing ;

Put n instead of 3 :


t(n) = t(1) + (n - 1)d

_________________________________

Step (3)

Stop right here.

Let's go to find the sum of the n first terms of the linear sequence.

Do you remember what did we do in step(1) ? Of course you do.

Let's do it again.


s = t(1) + t(2) + t(3) + ... + t(n) \\


s = t(n) + t(n - 1) + t(n - 2) + ... + t(2) + t(1) \\

According to the thing what we found in step(2) we have :


s = t(1) + ( \: t(1) + d \: ) + ( \: t(1) + 2d \: ) + ... + ( \: t(1) + (n - 1)d \: ) \\


s = ( \: t(1) + (n - 1)d \: ) + ( \: t(1) + (n - 2)d \: ) + ... + t(1) \\

Sum the two above equation's terms like this:


t(1) + t(1) + (n - 1)d = 2t(1) + (n - 1)d \\

And


t(1) + d +t(1) + (n - 2)d = 2t(1) + d(n - 2 + 1) = 2t(1) + (n - 1)d \\

And the others like this.

We had n terms so we sumed n terms.

So we have :


2s = n * ( \: 2t(1) + (n - 1)d \: )

Divided the sides of the equation by 2


s(n) = (n)/(2) * ( \: 2t(1) + (n - 1)d \: ) \\

_________________________________

And we're done.

Thanks for watching buddy good luck.

♥️♥️♥️♥️♥️

User Pavel Sharanda
by
6.1k points